Quantitative Sensory Testing in Painful Hand Osteoarthritis Demonstrates Features of Peripheral Sensitisation. (14th November 2012) - Wajed, Julekha; Ejindu, Vivian; Heron, Christine; Hermansson, Monika; Kiely, Patrick; Sofat, Nidhi
Abstract : Hand osteoarthritis (HOA) is a prevalent condition for which treatments are based on analgesia and physical therapies. Our primary objective was to evaluate pain perception in participants with HOA by assessing the characteristics of nodal involvement, pain threshold in each hand joint, and radiological severity. We hypothesised that inflammation in hand osteoarthritis joints enhances sensitivity and firing of peripheral nociceptors, thereby causing chronic pain. Participants with proximal and distal interphalangeal (PIP and DIP) joint HOA and non-OA controls were recruited. Clinical parameters of joint involvement were measured including clinical nodes, VAS (visual analogue score) for pain (0–100 mm scale), HAQ (health assessment questionnaire), and Kellgren-Lawrence scores for radiological severity and pain threshold measurement were performed. The mean VAS in HOA participants was 59.3 mm ± 8.19 compared with 4.0 mm ± 1.89 in the control group (P < 0.0001 ). Quantitative sensory testing (QST) demonstrated lower pain thresholds in DIP/PIP joints and other subgroups in the OA group including the thumb, metacarpophalangeal (MCPs), joints, and wrists (P < 0.008 ) but not in controls (P = 0.348 ). Our data demonstrate that HOA subjects are sensitised to pain due to increased firing of peripheral nociceptors. Future work to evaluate mechanisms of peripheral sensitisation warrants further investigation.